Comparative carbon accounting of multi-stream food waste management: insights from a megacity case study - Yang, Guodong; Zhang, Zuotai; Yan, Feng; Jiang, Jianguo; Gao, Yuchen; Chen, Shuling; Fangninou, Fangnon Firmin; Wang, Xiaoxiang (Frontiers in Environmental Science, 2026)
BackgroundFood waste (FW) management can contribute to emission reduction when low-carbon pathways such as anaerobic digestion or composting are adopted instead of landfilling.MethodsThis study quantified emissions across four treatment modules for five household (HHFW), one kitchen (KW), and two fruit and vegetable (FVW) waste sites.ResultsBaseline operations emitted 66,086.2 t CO2, with HHFW and KW contributing 69.9% and 22.9%, respectively. Pollutant treatment dominated (93.4%), mainly from residue and sewage management. FW intensities ranged from 54.34–162.13 kg CO2/t-HHFW, 122.1 kg CO2/t-KW, and 59.2–84.3 kg CO2/t-FVW. Resource recovery presented both offsets and burdens: grease recycling avoided up to −10.87 kg CO2/t-KW, while composting added 74.7 kg CO2/t-FVW. Compared to landfill disposal, the project reduced carbon intensity 7–16 fold, exceeding 800 kg CO2/t at top-performing sites (V1 and H4). Relative to incineration, reductions were smaller and site-dependent, though most treatment streams still achieved net savings. Scenario optimization highlighted the transformative potential of advanced interventions: a Moderate pathway integrating anaerobic acid production (AOP) cut emissions 1.6–1.7 fold, while optimistic pathways, anaerobic digestion (AD) and insect bioconversion (BSFL), achieved net-negative emissions of −308.4 kg CO2/t for HHFW and −117.41 kg CO2/t for FVW, respectively.ConclusionThese findings demonstrate that source separation, targeted resource recovery, and coupling bioenergy with value-added products can convert FW management from a carbon source to a net sink, supporting deep decarbonization strategies.